Analisis Strategi Pengembangan Community Based Tourism Pariwisata Berkelanjutan di Kabupaten Ende: Studi pada Desa Watu Raka Kecamatan Kelimutu Kabupaten Ende - Ichsan Abdillah Hatta; Ernesta Leha; Hyronimus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the tourism potential that will be managed by the community based on community perceptions of existing tourism potential, determine tourism management strategies and evaluate community-based tourism activities through perceptions. The method used is qualitative with a descriptive approach. Data collection was carried out through in-depth interviews with village residents who are tourism entrepreneurs. Data analysis uses IFAS EFAS analysis and SWOT analysis. The research results show that the Community Based Tourism development strategy has not been implemented optimally because it has not been able to increase the tourist attraction of Watu Raka Village as a tourist destination.